FORMULATION OF SNAKEHEAD FISH (CHANNA STRIATA) AND SUNGKAI LEAF (ALBERTISIA PAPUANA BECC) ON THE QUALITY OF SHREDDED - Suparno Suparno; Odi Andanu (Universitas Darussalam Gontor, 2023)
This study aims to determine the effect of the formulation of shredded snakehead fish and sungkai leaf on the quality of shredded to produce quality shredded. The design of this study used a non-factorial Completely Randomized Design (CRD) with 4 (four) treatments and 6 (six) repetitions, namely: P1 = 100 g snakehead fish; P2 = 99 g of snakehead fish: 1.0 g of sungkai leaf powder; P3 = 98 g of snakehead fish: 2.0 g of sungkai leaf powder; P4 = 97 g of snakehead fish: 3.0 g of sungkai leaf powder. The results of the research on the effect of the formulation of shredded snakehead fish with the addition of sungkai leaf powder on chemical properties showed results that significantly affected ash content 47.37% - 5.81%, water content 5.16% - 5.66%, protein content 27.36 % - 51.21%, fat content 18.06 - 22.41%, antioxidant activity 47.81 - 103.96 µg/ml, and hedonic tests such as color 3.00 - 5.44, aroma 4.16 - 5 .04, taste 3.96 – 5.80 while the texture has no significant effect. The treatment of the formulation of shredded snakehead fish with the addition of sungkai leaves complies with the Indonesian National Standard (SNI).